2017
DOI: 10.1001/jamaophthalmol.2017.1012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Dynamic Contour Tonometry, Uncorrected and Corrected Goldmann Applanation Tonometry, and Stage of Glaucoma

Abstract: IMPORTANCE Accurate determination of intraocular pressure (IOP) is crucial for the diagnosis and management of glaucoma. Objective clinical evaluation of the correction equations for Goldmann applanation tonometry (GAT) is lacking. OBJECTIVES To investigate the difference between corrected and conventional GAT and Pascal dynamic contour tonometry (DCT) measurements, as well as the correlation between discordant IOP values and stage of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Subsequently we applied five modifications or corrections reviewed in [14] and our simple numerical simulation method based on ORA and proposed in [15]. The obtained results are presented in Fig.…”
Section: Tab 1 Individual Parameters Of Measured Subjects and Their Iopmentioning
confidence: 99%
“…Subsequently we applied five modifications or corrections reviewed in [14] and our simple numerical simulation method based on ORA and proposed in [15]. The obtained results are presented in Fig.…”
Section: Tab 1 Individual Parameters Of Measured Subjects and Their Iopmentioning
confidence: 99%
“…Concerning the comparison between DCT and GAT correcting formulas 29 31 , our results aren’t always in agreement.…”
Section: Discussionmentioning
confidence: 58%
“…[ 24 ] The use of such correction formulas is debatable, and a recent report found that the application such formulas did not yield better agreement between GAT and DCT. [ 25 26 ] As our primary goal was agreement between devices, no such correction was utilized in our study.…”
Section: Discussionmentioning
confidence: 99%